2016
DOI: 10.3343/alm.2016.36.6.536
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Major Methicillin-Resistant Staphylococcus aureus Clones in Korea Between 2001 and 2008

Abstract: BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) are important pathogens causing nosocomial infections in Korean hospitals. This study aimed to investigate the epidemiological and genetic diversity of clinical S. aureus isolates in healthcare settings from 2001 to 2008.MethodsSamples and data were obtained from 986 individuals as part of the National Antimicrobial Surveillance Project, involving 10 regions nationwide. Molecular typing studies, including multilocus sequence typing (MLST) and staphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
2
11
0
1
Order By: Relevance
“…According to several studies, CC5 is the main CC detected in the Americas and Asia. 55 , 63–65 We observed the same trend, since of the 14 clones, 50% were grouped into CC5 (69%), followed by CC8 (8.4%). CC5 is more common in MRSA with SCC mec -II, and CC8 has been associated with MRSA-SCC mec -IV isolates with PVL, which leads to more serious clinical conditions, in particular fulminant pneumonia or deep vein thrombosis.…”
Section: Discussionsupporting
confidence: 70%
“…According to several studies, CC5 is the main CC detected in the Americas and Asia. 55 , 63–65 We observed the same trend, since of the 14 clones, 50% were grouped into CC5 (69%), followed by CC8 (8.4%). CC5 is more common in MRSA with SCC mec -II, and CC8 has been associated with MRSA-SCC mec -IV isolates with PVL, which leads to more serious clinical conditions, in particular fulminant pneumonia or deep vein thrombosis.…”
Section: Discussionsupporting
confidence: 70%
“…ST72 MRSA seemed to play a major role in the spread of CA-MRSA to the hospital via COHA transfer. The prevalence of ST239 has recently decreased in Korea [6830], and ST72 MRSA has been found to be the most common clone in both CA- and HA-MRSA infections in Korean pediatric patients [1331]. The absence of ST239 and the presence of only a few major MRSA strains in this hospital provide evidence of the clonal spread of MRSA, indicating that a rapid change in MRSA clones is possible in a hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, MRSA is highly endemic, constituting 60–81% of clinical S. aureus isolates [56] and 58–64% of bacteremic isolates; ST5-SCC mec type II is the most prevalent HA-MRSA [78910]. HA-MRSA strains have spread to the community [12].…”
Section: Introductionmentioning
confidence: 99%
“…These differences can be attributed to variations in microbiological methods (sampling technique, culture sites, and method of MRSA identification), local infection control standards, and the local prevalence of MRSA. Gi et al [32] reported that the methicillin resistance rate of staphylococcal isolates in Korea is slightly higher than that in other countries. Another study showed that the prevalence of MRSA is 73% among the nosocomial S. aureus isolates in Korea, which is higher than that in other Asian countries [21].…”
Section: Discussionmentioning
confidence: 99%